(untitled) - Trigilio, John (Indianapolis, Ind., 2005)
This friendly, approachable guide introduces readers to the famous and infamous women of Scripture, describing in everyday language the contributions these women made in their time and ours. From Eve, Sarah, and Esther to Mary and Mary Magdalene, it discusses well-known women of both the Old and New Testaments, examining their role in Biblical narratives, their place in the Jewish and Christian faiths, and the lessons their stories impart to women today
Keywords: Women in the Bible,Phụ nữ trong Kinh Thánh